The moderating role of transformational leadership on the relationship between deviant workplace behaviors and employee turnover intentions in China - Qi, Linkai; Chaudhary, Naveed Iqbal; Yao, Kai; Mirza, Farhan; Khalid, Rabia (Frontiers in Psychology, 2022)
This study aimed to analyze the effect of deviant workplace behaviors such as mistreatment, bullying, and incivility on employee turnover intention and identify the transformational leadership role as a moderator. The data was collected through a survey questionnaire with the help of a purposive sampling technique. A total of 318 respondents' data was gathered from university academic and general staff in China. The results were analyzed through SPSS and structural equation modeling SEM software. The findings indicate that deviant workplace behavior, i.e., mistreatment, bullying, and incivility, significantly affect employee turnover intention. Moreover, a result shows that transformational leadership has a significant moderating role on the relationship between turnover intention and workplace bullying and incivility but was insignificant between turnover intention and workplace mistreatment. Lastly, implications and limitations were also discussed in this article.